CODE-SWITCHING IN ENGLISH DEBATING CLASS: CASE STUDY AT UNIVERSITY OF MUSLIM NUSANTARA Al-WASLIYAH - Sapitri, Reni (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Debate is one of the lectures which encourage the learners to think critically and speak fluently in English. However, when the learners communicate their ideas in the debate classroom, many learners are find it difficult to express their ideas and use code-switching to explain their understanding. This paper presents the results of a single case study of an EFL learners’ code switching in English debating class in term of types and reason of code switching occurs during debate. The result of the research indicated that all of learners’ code switching are based on the intra-sentential type. Further, one of the reason why code-switching occurs in English debating classroom is due to the learners’ falters during expressing their arguments. They felt nervous when expressing their arguments.The subject of the research are the learners from class IIIA and IIIB which consist of 75 learners majoring in English at Universitas Muslim Nusantara Al-wasliyah.